Optimal AGC of a power system incorporated BESS-EHVAC/DC link using evolutionary techniques - Ashwini Kumar; Omveer Singh (Institute of Advanced Engineering and Science, 2023)
This research paper reveals the design of controller with optimization techniques for automatic generation control (AGC) in multi-area power system incorporated with diverse energy sources. The diverse sources are conventional thermal, hydro and gas power station (THG). The frequency deviations should be remains constant in modern power systems. Optimization techniques used for proposed model for proportional integral (PI) controller which is tuned for AGC with diverse energy sources. The battery energy storage system (BESS) and extra high voltage alternating current/ direct current (EHVAC/DC) link investigated with proposed model.Â The proposed model has been tested with 1% step load perturbation (SLP) and MATLAB/Simulink verified their results. All the simulation results justified the area control error (ACE) with frequency deviation & tie-line power flow for area-1 and area-2. The comparative study done for PI controller with GA & PSO in the proposed model. It has shown its efficacy with proposed model including BESS and EHVAC/DC- link using GA and PSO.